Pemberdayaan Kader Posyandu Lansia Untuk Pencegahan Hipertensi dan Komplikasinya di Purwokerto - Yunita Sari; Made Sumarwati; Eman Sutrisna (Jurnal Pengabdian Pada Masyarakat, 2018)
EMPOWERMENT OF ELDERLY POSYANDU CADRES FOR PREVENTING HYPERTENSION AND ITS COMPLICATION IN PURWOKERTO. The highest prevalence of degenerative diseases in Banyumas regency is hypertension. The prevention of hypertension in elderly could be done by Elderly Posyandu. However, there are many problems which occur in Elderly Posyandu of Soka Nirmala III and Sejahtera II in preventing hypertension and its complication, such as the limitation of materials for blood pressure measurement, lack of knowledge for hypertension management, lack of knowledge about self-treatment for reducing blood pressure. The purposes of this programme were to give kits for hypertension measurement to elderly posyandu, to conduct training of hypertension prevention, training about diet management, training about elderly exercise, training about self-treatment for reducing blood pressure. This community service was done through health education, training, and simulation. This community service could improve the knowledge of cadres and elderly in managing hypertension, improve knowledge in conducting exercise for reducing hypertension, improve knowledge in diet management, and improve the knowledge about self-treatment for reducing hypertension. It is expected that the prevalence of hypertension and its complication could be reduced and the quality of life of elderly could be improved.